Knee and hip articular cartilage have distinct epigenomic landscapes: implications for future cartilage regeneration approaches. Issue 12 (26th September 2014) - den Hollander, W; Ramos, Y F M; Bos, S D; Bomer, N; van der Breggen, R; Lakenberg, N; de Dijcker, W J; Duijnisveld, Bouke J; Slagboom, P E; Nelissen, Rob G H H; Meulenbelt, I
Abstract : Objectives: To elucidate the functional epigenomic landscape of articular cartilage in osteoarthritis (OA) affected knee and hip joints in relation to gene expression. Methods: Using Illumina Infinium HumanMethylation450 BeadChip arrays, genome-wide DNA methylation was measured in 31 preserved and lesioned cartilage sample pairs (14 knees and 17 hips) from patients who underwent a total joint replacement due to primary OA. Using previously published genome-wide expression data of 33 pairs of cartilage samples, of which 13 pairs were overlapping with the current methylation dataset, we assessed gene expression differences in differentially methylated regions (DMRs). Results: Principal component analysis of the methylation data revealed distinct clustering of knee and hip samples, irrespective of OA pathophysiology. A total of 6272 CpG dinucleotides were differentially methylated between the two joints, comprising a total of 357 DMRs containing 1817 CpGs and 245 unique genes. Enrichment analysis of genes proximal of the DMRs revealed significant enrichment for developmental pathways and homeobox (HOX) genes. Subsequent transcriptomic analysis of DMR genes exposed distinct knee and hip expression patterns. Conclusions: Our findings reveal consistent DMRs between knee and hip articular cartilage that marked transcriptomic differences among HOX genes, which were not reflecting the temporal sequential HOX expression pattern during development. This implies distinct mechanisms for maintaining cartilage integrity in adulthood, thereby contributing to our understanding of cartilage homeostasis and future tissue regeneration approaches.